The Influence of Local Wisdom in The Decision Making Process - Ermina Istiqomah; Sudjatmiko Setyobudihono; M Azra Inan Abdillah (Fakultas Kedokteran Universitas Lambung Mangkurat, 2018)
Abstract: The existence of an authoritative figure is an indivisible part of society living in Indonesia. The high claims of iron tablets in pregnant women were indicated not followed by high consumption of Fe tablets. Motivation was suspected to be a problem in various treatment processes. The aim of this research was to know the level of influence in influencing the decision and also the perception of various influence roles based on the understanding of local wisdom. Descriptive method was used by using a closed questionnaire to 130 respondents. The results showed that the husband, the parents and the mother-in-law were the individuals who had an influence on the decision of a pregnant woman. The need for permission was the highest factor chosen regarding the participation in the health program. This study provides an overview of the influence of individuals that must be considered in making a health program for pregnant women. Keywords: health program, influence of individual, local wisdom, pregnant mother